PROFESSIONAL CHOICE OF HIGH SCHOOL STUDENTS AND FACTORS OF CHANGE - Shnarbekova, Meruyert (Farabi Journal of Social Sciences, 2025)
Purpose. This article investigates the factors influencing career choices among high school students in Kazakhstan, with a particular focus on the impact of gender and school type. The study aims to identify the key motives and conditions shaping students’ professional self-determination during adolescence. Design/methodology/approach. The research is grounded in sociological and psychological theories, including the theory of professional self-determination and the concept of professional identity. A quantitative sociological survey was conducted among 9th and 11th grade students from both urban and rural schools. The sample included 1,000 students aged 15 to 17, selected through targeted sampling based on region, school type, and gender. Data were collected using a structured questionnaire. Findings. The findings reveal that career choices among students are significantly influenced by a range of social and institutional factors, such as family background, education system characteristics, and labor market conditions. The study also identifies notable differences in career preferences by gender and school type, underscoring the importance of tailoring career guidance to individual socio-demographic contexts. Originality. This study contributes to the understanding of professional orientation processes in Kazakhstan by providing empirical insights into the diverse factors that shape students’ career decisions. It highlights the need for differentiated and personalized career support strategies in educational policy and practice. Key words: career choice, sociological survey, career guidance, professional self-determination